2019
DOI: 10.1002/jsfa.10001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of T‐2 toxin on the muscle proteins of shrimp (Litopenaeus vannamei) – a proteomics study

Abstract: BACKGROUND: T-2 toxin (T-2) is a potent mycotoxin and a common contaminant of aquatic animal feed, posing a serious risk to health and aquatic animals. We investigated the effect of T-2 on shrimp muscle proteins using proteomics and conventional biochemical methods. Shrimp were fed a diet containing T-2 at 0-12.2 mg kg −1 for 20 days, and changes to the muscle protein composition, ATPase activities, and the sulfhydryl (SH) content and hydrophobicity of actomyosin (AM) were determined. A proteomics study of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…Myofibrillar proteins regulate the contraction of muscle fibers, including myosin, actin, and tropomyosin 35 . Previous studies have found that exposure to T‐2 toxin alters the content of myofibrillar proteins according to the rule ‘low‐dose stimulation, high‐dose inhibition’ 8 . The current study also found that the myofibrillar protein content was increased in the early stage of T‐2 toxin exposure, and decreased in the middle and late stages.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Myofibrillar proteins regulate the contraction of muscle fibers, including myosin, actin, and tropomyosin 35 . Previous studies have found that exposure to T‐2 toxin alters the content of myofibrillar proteins according to the rule ‘low‐dose stimulation, high‐dose inhibition’ 8 . The current study also found that the myofibrillar protein content was increased in the early stage of T‐2 toxin exposure, and decreased in the middle and late stages.…”
Section: Discussionsupporting
confidence: 73%
“…The muscle proteins of shrimp can be classified as water‐soluble proteins, salt‐soluble proteins, alkali‐soluble proteins, and insoluble proteins 8 . Sarcoplasmic proteins and myofibrillar proteins are the main water‐soluble proteins and salt‐soluble proteins, respectively 8 . The results of this study indicated that, compared with the control group, exposure to T‐2 toxin resulted in a significant decrease in the sarcoplasmic protein content of shrimp muscle ( P < 0.05) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The protein content of tofu was determined using the Kjeldahl method, according to Huang et al., (2020). The protein conversion factor was 6.25.…”
Section: Methodsmentioning
confidence: 99%